2015
DOI: 10.1097/md.0000000000001073
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Children With Poor Cochlear Implantation Outcomes Using Massively Parallel Sequencing

Abstract: Cochlear implantation is currently the treatment of choice for children with severe to profound hearing impairment. However, the outcomes with cochlear implants (CIs) vary significantly among recipients. The purpose of the present study is to identify the genetic determinants of poor CI outcomes. Twelve children with poor CI outcomes (the “cases”) and 30 “matched controls” with good CI outcomes were subjected to comprehensive genetic analyses using massively parallel sequencing, which targeted 129 known deafne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 64 publications
4
64
0
Order By: Relevance
“…However, this limitation could be overcome with the availability of high‐throughput DNA sequencing to address paediatric SNHI. By simultaneously screening 129 deafness genes using the massively parallel sequencing technique, our recent study demonstrated that mutations in DFNB59 and PCDH15 , two genes expressed in the spiral ganglion neurons and/or brainstem auditory nuclei, were associated with unfavourable CI outcomes . Second, as in most previous reports, all 10 patients with OTOF mutations in this study had stationary severe‐to‐profound hearing levels before surgery, and the decision to perform cochlear implantation in these patients at an earlier age is less controversial.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, this limitation could be overcome with the availability of high‐throughput DNA sequencing to address paediatric SNHI. By simultaneously screening 129 deafness genes using the massively parallel sequencing technique, our recent study demonstrated that mutations in DFNB59 and PCDH15 , two genes expressed in the spiral ganglion neurons and/or brainstem auditory nuclei, were associated with unfavourable CI outcomes . Second, as in most previous reports, all 10 patients with OTOF mutations in this study had stationary severe‐to‐profound hearing levels before surgery, and the decision to perform cochlear implantation in these patients at an earlier age is less controversial.…”
Section: Discussionsupporting
confidence: 61%
“…The decision to undertake cochlear implantation is further complicated by the fact that improvement of auditory phenotypes with age may be observed in approximately 20% of children with ANSD . Recent studies have shown that genetic testing is of great help in determining the site of pathology in paediatric sensorineural hearing impairment (SNHI) . Specifically, mutations in the OTOF gene, a common cause of clinical ANSD, are an indicator that the pathology is confined to the synapse; post‐synaptic neurons and nerve fibres are preserved for electrical stimulation of CI.…”
Section: Introductionmentioning
confidence: 99%
“…One study that included 81 subjects with post-lingual hearing loss showed that CI users with genetic mutations in the sensory partition performed well after cochlear implantation, but no statistical analysis was performed (Miyagawa et al, 2016). A case-control study examined pediatric patients with good performance (n=30) and poor performance (n=12) and showed that genetic mutations in the sensory partition were more common in the high performing group, and that a specific mutation in spiral ganglion neurons ( DFNB59 p.Gly292Arg) was significantly more common in the poor performing group (Wu et al, 2015). Our goal was to further examine this relationship using a large number of subjects and comprehensive genetic testing which incorporates examination of causative genetic mutations affecting the spiral ganglion but also deleterious genetic variants that may independently affect this structure.…”
Section: Introductionmentioning
confidence: 99%
“…The sequencing methods and analysis pipelines have been previously reported 27, 28 . In brief, genomic DNA was fragmented into 800 bps.…”
Section: Methodsmentioning
confidence: 99%